The trend in exclusive breastfeeding practice and its association with maternal employment in Bangladesh: A multilevel analysis - Ahmmed, Foyez; Hossain, Md. Jamal; Sutopa, Tasmiah Sad; Al-Mamun, Md.; Alam, Morshed; Islam, Md. Rabiul; Sharma, Rohit; Sarker, Md. Moklesur Rahman; Azlina, Mohd Fahami Nur (Frontiers in Public Health, 2022)
Exclusive breastfeeding (EBF) is essential for infant and child health. This study aimed to explore the trend in the EBF over the last decade in Bangladesh and investigated if there was a significant association with maternal employment by analyzing the data extracted from three consecutive nationally representative surveys Bangladesh Demographic and Health Surveys (BDHS) of 2011, 2014, and 2017-18. Prevalence of EBF (95% confidence interval) with Cochran-Armitage test was reported to see the trend in EBF. A chi-square (χ2) test was applied to find the potential factors associated with EBF. Finally, a three-level logistic regression was utilized to find the significant association between maternal employment and EBF while adjusting other covariates. We observed no increase in the practice of EBF over the last decade (P = 0.632). Prevalence of EBF was 64.9% (95% CI: 61.41, 68.18) in 2011, followed by 60.1% (95% CI: 56.25, 64) in 2014 and 64.9% (95% CI: 61.82, 67.91) in 2017. Regression results showed that employed mothers had 24% (p<0.05) lower odds of EBF than unemployed mothers. Early initiation of breastfeeding was also found to be significantly associated [Adjusted odds ratio (AOR): 1.22, P<0.05] with EBF. Government and policymakers must come forward with new interventions to increase the practice of EBF, providing basic education and campaign on EBF. Maternity leave should be extended up to six months of the child’s age to achieve an optimal level of EBF.